First characterization of a canine parvovirus causing fatal disease in coatis (Nasua nasua) - Bucafusco, Danilo; Argibay, Hernán Darío; Diaz, Leandro; Vega, Celina Guadalupe; Minatel, Leonardo; Postma, Gabriela C.; Rinas, Miguel; Bratanich, Ana Cristi (Springer, 2020)
A canine parvovirus (CPV)-like virus was detected by PCR and isolated from dead coatis in Argentina. Analysis of the full-length genome sequence revealed that it resembled CPV-but also contained a mutation in the VP2 protein (Arg377Ser) that has not been described previously. This is the first report of a CPV-like virus producing clinical disease in coatis. Genetic similarity to CPV-2c viruses detected in Brazil suggests a strong relationship between these viruses. Although the pathogenic potential of CPV- and feline panleukopenia virus (FPV)-like strains in wild animals is still not completely understood, this study highlights the importance of parvoviruses as a threat to wildlife if proper conditions are present.